A New Species of the Genus Tropidophorus Duméril, Bibron, 1839 (Reptilia: Squamata: Scincidae) from China-Vietnam Border Region in Southeastern Yunnan Province, China - Wang, Kai; Li, Ling; Mu, Hao-Nan; Xu, Sheng-Jing; Che, Jing (Zootaxa, 2024)
Based on morphological and genetic data, we describe a new species of Tropidophorus from the tropical karst landscape in southeastern Yunnan Province, China, close to the Vietnam border. Phylogenetically, the new species forms a clade with T. baviensis, T. murphyi, and T. hainanus, with p-distances ranging from 4.7–5.1% for the 16S gene and 3.9–6.8% for 12S gene. Morphologically, the new species shares the karst morphotype of Tropidophorus, particularly similar as T. murphyi and T. baviensis, in which all having a dorsally compressed head and body, smooth dorsal head scales, and distinctively keeled body scales. However, the new species can be distinguished from these similar species by numbers of supralabial scales, ventral scales, scales around the tail at the10th subcaudal, and a larger body size. We emphasize the urgency of conservation for the tropical karst landscape in northern Indochina.